2017
DOI: 10.1007/s11136-017-1617-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subjective and actigraphy-measured sleep in 237 patients with metastatic colorectal cancer

Abstract: Objective Patients with cancers frequently experience sleep and circadian dysfunction. To date, only a few studies have used both a questionnaire and actigraphy for concomitant evaluation of sleep and circadian function in patients with cancer. We sought to evaluate objective sleep and circadian parameters in metastatic colon cancer (MCC) patients and their associations with symptoms and quality of life (QOL). Methods Patients reported subjective sleep problems on the EORTC QLQ-C30. Sleep and circadian param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…TST was underestimated with approximately one hour compared to subjective reports . Several other studies have confirmed this systematic underestimation in several chronic pain pathologies . Second, the Bland and Altman plot also revealed that patients who slept for a shorter period, underestimated their TST to a higher degree than patients with a longer TST.…”
Section: Discussionmentioning
confidence: 66%
“…TST was underestimated with approximately one hour compared to subjective reports . Several other studies have confirmed this systematic underestimation in several chronic pain pathologies . Second, the Bland and Altman plot also revealed that patients who slept for a shorter period, underestimated their TST to a higher degree than patients with a longer TST.…”
Section: Discussionmentioning
confidence: 66%
“…A more sophisticated approach would require quantitative analysis of rhythms, perhaps via software able to process real-time physiological data, to identify: timing of peaks (or troughs) enabling phase shift determination; amplitude of variation, from peak to trough; and the consistency of the rhythm over days. Techniques to achieve this are commonly used in the experimental setting [ 89 ], but have yet to transfer across to clinical practice. Medical education in the future may need to provide clinicians with the mathematical competence to handle more complex data relating to biological rhythms, or to use algorithms for their interpretation.…”
Section: Current Challenges and Future Perspectives On The Monitoringmentioning
confidence: 99%
“…Incorporation of such a measurement would allow for greater comparability with previous studies, and may prove more robust than objective actigraphy alone. 17 , 18 , 110 Therefore, this review recommends future research should report raw accelerometer movement data, in actigraphy-based studies, where possible. This should also be accompanied by a validated self-report sleep measure.…”
Section: Discussionmentioning
confidence: 99%
“…Modern sleep research has capitalized on advancements in wearable technology to provide objective measures of sleep in the free-living environment. [15][16][17][18] Actigraphy is the most common method, and involves participants wearing a personal accelerometer device, normally on the wrist, to record movement during sleep. [19][20][21] This movement data is then translated to provide information about a participants' sleep.…”
Section: Introductionmentioning
confidence: 99%